Pembuatan Laporan Keuangan Sederhana Berbasis Android dan Cloud untuk Peningkatan Literasi Keuangan UMKM - Haq, Aqamal; Iwan Ekawanto; Sri Susilowati (Dirkantara Indonesia, 2025)
This community service program aimed to improve the financial literacy of MSMEs in West Jakarta through training on preparing simple financial reports using Android-based applications and Cloud technology. The program involved 30 MSMEs under the West Jakarta Chamber of Commerce, representing trade, culinary, and service sectors. The training method combined lectures, hands-on practice with Android accounting applications, and the use of Cloud platforms for financial data management. Evaluation was conducted using pre-tests and post-tests. The results showed significant improvement: understanding of the importance of financial reports increased from 30% to 85%, the use of Android applications for recording transactions rose from 10% to 90%, and familiarity with Cloud technology grew from 20% to 75%. More than 85% of participants also expressed confidence in preparing financial reports to support access to external financing. This program highlights the importance of digital technology adoption for MSMEs as a step toward professional and competitive financial management.